2015
DOI: 10.1111/pin.12242
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus‐positive diffuse large B‐cell primary central nervous system lymphoma associated with organized chronic subdural hematoma: A case report and review of the literature

Abstract: We here report on a rare case of Epstein-Barr virus (EBV)-positive diffuse large B-cell lymphoma (DLBCL) detected in both brain parenchyma and in an organized chronic subdural hematoma (OCSH). A 96-year-old man diagnosed with asymptomatic OCSH in the left frontal convexity was referred to our hospital because of a de novo mass lesion just beneath the OCSH on contrast-enhanced magnetic resonance imaging. The size of the OCSH remained stable. We diagnosed the lesion as a malignant tumor. At surgery, the organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…7,8 Coagulopathy and intracranial tumors have been associated with spontaneous CSDH. 4,13,19,21 In this study we also found the association of hypertension, diabetes, previous surgery and Parkinson's disease associated with CSDH but they were all statistically insignifi cant causes. The presenting symptoms are depending on the site and size, confusion or coma, altered memory, speaking or swallowing problems, gait abnormalities, decreased mentation, headache, seizures and bowel or bladder incontinence.…”
Section: Chronic Subdural Hematomasupporting
confidence: 60%
See 2 more Smart Citations
“…7,8 Coagulopathy and intracranial tumors have been associated with spontaneous CSDH. 4,13,19,21 In this study we also found the association of hypertension, diabetes, previous surgery and Parkinson's disease associated with CSDH but they were all statistically insignifi cant causes. The presenting symptoms are depending on the site and size, confusion or coma, altered memory, speaking or swallowing problems, gait abnormalities, decreased mentation, headache, seizures and bowel or bladder incontinence.…”
Section: Chronic Subdural Hematomasupporting
confidence: 60%
“…Epidemiological and demographical data like age, sex, mode of injury if recorded, alcohol intake, comorbid conditions, side of hematoma, admission Glasgow coma scale (GCS) and GCS at discharge were noted. The outcome of surgery for CSDH is good and therefore the GCS was dichotomized into good (GCS-15) or poor prognosis (GCS- [12][13][14] and this was used to calculate the fi nal outcome and interrelationship between variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, despite aggressive histologic features (large cell morphology, high proliferation index), FA-DLBCL is a localized disease with an indolent behaviour and a favourable outcome even with surgical excision alone. The rare event of relapse and the associated risk of local invasion [3,9,21], however, reinforces the need for a complete surgical excision.…”
Section: Fa-dlbcl Is Invariably Ebv-positivementioning
confidence: 99%
“…As reviewed by Boyer et al, three cases of fibrin-associated DLBL have been documented in SDH found in patients with a median age of 66.5 years and a male: female ratio of 4:0. An additional new case was reported by Boyer et al All except one of these cases showed similar histology, prognosis and an EBV-association [ 1 , 2 , 6 ]. One of the cases was considered a primary lymphoma presenting as a chronic subdural hematoma [ 2 ].…”
mentioning
confidence: 99%